CONTAMINATED LAND LEGISLATION IN CHINA: STATUS QUO AND CHALLENGES - ZHAO, Xiaobo (Journal of Environmental Management and Tourism, 2011)
China is experiencing increased land contamination in recent years. A number of social and economic problems have developed and must be dealt with, in some cases, as a matter of urgency. Those problems have been neglected for years and so far there is no nationwide specific legislation to address the contaminated land issue. However, numerous relevant provisions on addressing soil or land protections can be found under the current legal system, particularly in the context of environmental regulatory system. Those provisions address broad issues which include soil quality protection, land reclamation, land use planning and relevant liabilities. This paper explores the regulatory frameworks for addressing contaminated land issues. It concludes that the current regulatory framework in China can not fully address contaminated land problems, thus a specific legislation at the national level is imminently required.